Simulation on temperature distribution of oil palm empty fruit bunches during the microwave pyrolysis process - Hussain, Siti Aslina; Bano, Shaista; Yeoh, Hooi Sim; Omar, Rozita (John Wiley & Sons, 2014)
Oil palm empty fruit bunches (EFB) is a plentiful agricultural waste in Malaysia, which can be further processed to increase its calorific value for fuel purposes and as a value-added product. Microwave pyrolysis is a promising technology that can convert the EFB into bio-oil, char and synthesis gas without cracking the EFB surface because of overheating. Computational fluid dynamics (ansysTM cfx 13.0, ANSYS, Inc. Southpointe, 275 Technology Drive, Canonsburg, PA 15317, U.S.A.) was used in a 3-D model to predict the temperature distribution of the EFB model in a microwave-heated reactor during the pyrolysis process. The parameters under investigation include heating source orientation, nitrogen gas flow rate, microwave power intensity and microwave absorber efficiency, which have an important role in pyrolysis optimisation. The results show that heating source orientation and nitrogen gas flow rate did not affect the EFB temperature profiles. However, microwave power intensity has a linear relationship with the EFB temperature at different microwave absorber efficiencies.